Perancangan dan Pengembangan Website Inventory dan Laporan Keuangan Pada Warung Sembako Akai - Junifer Junifer (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Warung Akai is a business that engaged in selling basic necessities since 2016. From the beginning of its operation until now, Warung Akai uses a manual recording system in an ordinary cash book to process every store transaction. This causes omissions in data recording and shop owners also experience difficulties in planning for store expansion in the future because they cannot clearly know the financial and stock condition of the store. This study aims to solve the problems faced by Warung Akai in recording data and processing financial reports. This research produces a web-based accounting information system that is able to record all store transactions from sales, purchases, stock of goods, to processing financial reports. This accounting information system is designed using the PHP, HTML and CSS programming languages and uses XAMPP as a localhost web server. The implementation of the accounting information system has succeeded in increasing efficiency and effectiveness in recording transactions, planning inventory and processing Warung Akai's financial reports.